Peran Early Goal Directed Therapy (EGDT) dalam Managemen Awal Sepsis Terhadap Mortalitas, Keseimbangan Cairan, dan Lama Perawatan: Tinjauan Sistematis - Fadilla Nur Safitri; Masfuri Masfuri; Muhamad Adam; Riri Maria (Jurnal Ners, 2026)
Sepsis is a life-threatening organ dysfunction. Early management of sepsis is key to preventing worsening of the patient's condition. Early Goal-Directed Therapy (EGDT) is a method of early sepsis management that has been used for the past 10 years and is an important intervention in the early care of sepsis, the effectiveness and implementation of which are increasingly developing. EGDT is believed to provide comprehensive sepsis management and provide better benefits to sepsis patients. This systematic review aims to compile research findings from the past 10 years regarding the role of EGDT on outcome variables that indicate improvement in sepsis patients. The literature search used PRISMA guidelines from seven database sources and publishers: Science Direct, ProQuest, PubMed, Clinical Key, Scopus, Taylor & Francis, and Springer Nature. Ten articles were subjected to research critique using JBI Critical Appraisal Tools. Several studies have shown that the implementation of EGDT shows significant improvements in mortality, fluid balance, and length of stay. Modification of EGDT with the use of ultrasonography or echocardiography in monitoring fluid responsiveness shows better results in the initial management of sepsis.